Análisis físico- químico de las aguas subterráneas aledañas al canal de riego principal Machala Pasaje del Consejo Provincial de El Oro, provenientes del Río Jubones en el sitio Malecón en la ciudad de Pasaje. - Apolo Romero, Priscila P (2006)
The water like fundamental liquid for the life, is the most abundant component in the surface of our planet lamentably, 94% are salt water and she is no apt for the human consumption, rest 6%, is in the subsoil they are the same superficial waters, that have filtered, a part inside the terrestrial crush and have formed great internal deposits of water that sometimes appear and springs to the surface and other times wells take part the man perforating to extract it.